An interventional study on intensive care unit drug therapy assessment in a rural district hospital in India - Pichala, Priyanka Tejashwani (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Intensive care unit is a potential area for drug-related problems. As many of the patients treated are complex patients, clinical pharmacy intervention could find drug therapy problems. MATERIALS AND METHODS: Drug information liaisons daily attended ward rounds with intensivists and screened the patient for drug therapy assessment using the American Society for Health-System Pharmacists clinical skills competition DTA format. This was a prospective study done for 6 months from August 2012 to January 2013. Simple statistics were used to tabulate the drug-related problems assessed. RESULTS: A total of 72 patients were screened for drug therapy problems, for which 947 drug doses were prescribed in the study period. The total number of prescriptions was 148. The average number of drugs per prescription was 6.39 and the average number of drugs per patient was 13.15. A total of 243 problems were identified; on an average, 1.67 problems were present per prescription. The total number of drug interactions identified was N = 192 (78.2%); majority of them (61.4%) were of type C (not serious). So, 55.73% of them were monitored and not stopped or substituted. The second type of problem was a correlation between drug therapy and medical problem (7.4%). Appropriate drug selection and drug regimen was the third problem, and the adverse drug reactions and therapeutic duplications accounted for approximately 2% of the drug-related problems identified. CONCLUSION: Drug interactions constituted the major problem of ICUs, but not many were serious or significant. Consensus in assessment of drug-related problems and convincing intensivists with good quality evidences are required for better acceptance of interventions.